Hubungan Stres Psikososial Dengan Gangguan Siklus Menstruasi pada Siswi di SMA Katolik Karitas Tomohon - Kezia Mirachelly Suyoko; Nancy Sylvia Bawiling; Deviana Pratiwi Munthe (Jurnal Ilmiah Kesehatan, 2025)
Background of the study, psychosocial is one of all forms of stress will produce a body reaction. One of the most visible impacts of this stress is women's problems. There are many health problems, one of which is menstrual health problems. The purpose of this study was to determine the relationship between psychosocial stress and menstrual cycle disorders in female students at Karitas Catholic High School, Tomohon in 2024. The method in this study will be conducted at Karitas Tomohon Catholic High School, Paslaten Dua, Lingkungan II, East Tomohon, Tomohon City, North Sulawesi on December 6 to December 11, 2024. The sample of this study was 74 female students, taken by Total Sampling, This study is a quantitative study with a cross-sectional design, tested using chi-square. The results of this study showed a relationship between psychosocial stress and menstrual cycle disorders in female students at Karitas Catholic High School, Tomohon, in 2024, with a p-value = 0.025 <0.05. It is hoped that female students will build a good school environment and community as friends to tell stories, so that the level of psychosocial stress in the internalization aspect of female students at this school can be reduced.